Protection of Consumers Using Beauty Products Promoted by Marketing Influencers: A Comparative Study of the United States – Indonesia - Eliska Vioni; Ridha Wahyuni (KRTHA BHAYANGKARA, 2025)
This study aims to determine the legal regulations and responsibilities of Influencers towards consumers in carrying out marketing or promotional practices on social media related to dangerous beauty products and containing misleading claims, and how they compare with the legal regulations in the United States, as well as the legal efforts that can be taken by consumers who suffer losses due to these marketing practices. The method used in this study is normative juridical with a statutory approach (Statute Approach) and a comparative approach (comparative approach). The results of the study show that there are no legal regulations that specifically regulate Influencer marketing practices in Indonesia, based on the UUPK, legal responsibility for consumer losses is only borne by business actors because the position of Influencers cannot be categorized as advertising business actors. In the United States, business actors and influencers are burdened with their responsibilities because their positions have been regulated by the Federal Trade Commission (FTC). However, influencers in Indonesia can still be sued for disseminating misleading information, as per Article 28 (1) of the ITE Law and Article 1365 of the Civil Code, for the claims they make.